Prevalence of epicondylitis and elbow pain in the meat-processing industry. - Viikari-Juntura, Eira; Kurppa, Kari; Kuosma, Eeva; Huuskonen, Matti; Kuorinka, Ilkka; Ketola, Ritva; Konni, U. (Scandinavian Journal of Work, Environment & Health, 1991)
To determine the etiologic role of strenuous manual tasks in relation to epicondylitis, three clinical cross-sectional examinations were performed on meatcutters (N = 102), sausage makers (N = 125), packers (N = 150), and workers in nonstrenuous tasks (N = 332). The workers in strenuous jobs reported elbow symptoms 1.6-1.8 times as often as those in nonstrenuous jobs. Female sausage makers also showed epicondylar tenderness more often than the women in nonstrenuous jobs. In all the cross-sectional examinations combined, seven cases (0.8%) of epicondylitis were detected in both the strenuous and nonstrenuous jobs. A control for the possible sources of bias (leaving the company, changing task, being on sick leave) did not suggest a marked loss of potential cases of epicondylitis. A major role of strenuous tasks in the etiology of epicondylitis was not shown. However, because the number of clinical cases was small, the power of the study was low.